Managing a Library automation project: the Moi University experience - Ondari, Ezra Okemwa (MCB University Press, 1999)
Examines the major problems associated with managing a library automation project in a developing country. The Moi University experience is representative of the type of problems that a library project manager in a developing country is likely to face. Poor infrastructure, a shortage of local technical expertise, lack of information technology and a shortage of qualified managers are some of the managerial hurdles that they should be able to cope with. Training local personnel and equipping the training institutions may partly solve some of the problems. Management and information technology skills should be emphasised in whatever training programmes may be initiated in a bid to overcome the shortages
Keywords: Automation; Kenya; University libraries